Caring with confidence for Huntington's disease. Issue 4 (4th November 2014) - Dale, Maria; Freire-Patino, Dawn; Matthews, Helen
Abstract : Purpose: – The purpose of this paper is to describe the development of a psychoeducational support group for informal carers of people with Huntington's disease (HD). Design/methodology/approach: – A clinical intervention was designed by a specialist HD service in consultation with HD carers, building on resources from a generic programme for carers, to meet the specific needs of HD families. A mixed methods, repeated measures design was used to examine any potential benefits this had on carer confidence and quality of life, and to ascertain the most beneficial aspects of the programme. Findings: – At the end of the group, participants reported feeling more confident in caring for relatives with HD. Carers reported that gaining new information and being with other carers was helpful. Research limitations/implications: – Although participant numbers were small, this pilot indicates that informal carers of HD patients appear to value psychoeducational support delivered in a group format. Evaluation of this type of intervention for carers warrants more rigorous investigation. Originality/value: – There is a paucity of research that evaluates the impact of HD-specific carer interventions. This offers a description of a unique intervention that was aimed to increase knowledge and confidence among HD carers and to help provide the basis for more comprehensive services to be offered to carers of this devastating genetic illness.